Parasites in vegetables used for human consumption: a risk for public health - Macedo, Lucia Oliveira; Barros, Guilherme Mota Maciel Rego; Silva, Tatiene Rossana Móta; Carvalho, Gílcia Aparecida; Ramos, Rafael Antonio Nascimento (Medicina Veterinária, 2021)
Vegetables are pivotal food source to the human beings, representing the source of key nutrients, which in turn the occurrence of chronic diseases. Nonetheless, the consumption of poorly washed or in nature vegetables may expose individuals to the risk of infection by parasites. The aim of this study was to assess the contamination by parasites of medical and veterinary concern in raw vegetables used for human consumption. Fresh vegetables [i.e., lettuces (n = 50), carrots (n = 50) and beet (n = 50)] were acquired in different market places across the municipality of Garanhuns (northeastern Brazil) and the presence of parasites assessed by a sedimentation technique. Parasites were detected in 44.7% (67/150) of the evaluated samples. This study provides important data on the occurrence of zoonotic agents in vegetables. Therefore, strict hygienic measures should be adopted to reduce the risk for vegetable contamination leading to a reduction of human infection by pathogens of medical importance.